DIPLOMASI INDONESIA TERHADAP SINGAPURA DALAM PENETAPAN GARIS BATAS LAUT DI BAGIAN TIMUR SELAT SINGAPURA - Akmaludin "; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims analyze “Indonesian Diplomacy to Singapore in the determination of the sea border in the eastern part of the Singapore’s strait”. The boundary of Indonesian and Singapore comprise the region Singapore’s Strait. But the boundary of Indonesia and Singapore resolved yet. This condition will disturb Indonesia sovereignty in the region.This research use library research method. All data in this research from books, literatur, magazine articles, journals, bulletins, dokuments and websites. This research use theory diplomacy, especislly soft diplomacy that use negotiation as important point. This research use level analysis “Nation State” where the State is the dominant actor who used in interactive world.this research, concluded that the diplomacy of Indonesia to Singapore in the determination of the sea border in the eastern part of the Singapore’s Strait get to success. Indonesia refused the reclamation of Singapore is used as the baseline border, and baselines of Singapore using the normal baseline as a marker standing water line lower, while for Indonesia using the straight baselines and archipelagic baselines as conditions around boundary.Keywords: Diplomacy, Soft Diplomacy, Boundary, Baseline Border, Reclamation.